1992
DOI: 10.1126/science.258.5089.1760
|View full text |Cite
|
Sign up to set email alerts
|

Synchronism of the Siberian Traps and the Permian-Triassic Boundary

Abstract: Uranium-lead ages from an ion probe were taken for zircons from the ore-bearing Noril'sk I intrusion that is comagmatic with, and intrusive to, the Siberian Traps. These values match, within an experimental error of +/-4 million years, the dates for zircons extracted from a tuff at the Permian-Triassic (P-Tr) boundary. The results are consistent with the hypothesis that the P-Tr extinction was caused by the Siberian basaltic flood volcanism. It is likely that the eruption of these magmas was accompanied by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(166 citation statements)
references
References 24 publications
5
155
0
2
Order By: Relevance
“…Although no consensus has been reached so far on the causal mechanisms, the~250 Ma Siberian Traps is widely believed to be the ultimate cause of PTB mass extinction due to the coincidence of these two events (e.g., Campbell et al, 1992;Courtillot, 1994;Courtillot and Renne, 2003;Kamo et al, 2003Kamo et al, , 2006Racki and Wignall, 2005;Reichow et al, 2002;Renne et al, 1995). However, two potential pitfalls are associated with this methodology/reasoning: (a) If the two events took place at the same time, they are possibly but not necessarily related to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Although no consensus has been reached so far on the causal mechanisms, the~250 Ma Siberian Traps is widely believed to be the ultimate cause of PTB mass extinction due to the coincidence of these two events (e.g., Campbell et al, 1992;Courtillot, 1994;Courtillot and Renne, 2003;Kamo et al, 2003Kamo et al, , 2006Racki and Wignall, 2005;Reichow et al, 2002;Renne et al, 1995). However, two potential pitfalls are associated with this methodology/reasoning: (a) If the two events took place at the same time, they are possibly but not necessarily related to each other.…”
Section: Introductionmentioning
confidence: 99%
“…However, this trend sharply reverses near the Middle/Late Permian boundary at a time when chert deposition appears to have increased worldwide. Likewise, the end-Permian massive eruption of the Siberian traps (Campbell et al, 1992;Renne et al, 1995) coincides with the collapse, not the outburst, of chert factories around the world.…”
Section: Formation and Preservation Of Biogenic Chertmentioning
confidence: 99%
“…(Shishkin et al, 1986) has been reported form the lower Norilskian basalts of the Tungusska Basin, Siberia (A proposed candidate for the continental GSSP of the Permian-Triassic boundary (Lozovsky, 1998)). The Norilsky region intrusions are correlated to the Mokulaevskyi basalt (248±4 Ma; Campbell et al, 1992). If this occurrence of Lystrosaurus can be confirmed it would imply a Late Permian-Early Triassic age for the first occurrence of Lystrosaurus within these strata.…”
Section: Introductionmentioning
confidence: 99%